Surface modification and structure analysis of coated iron oxide yellow pigments to improve dispersion in organic solvents. (22nd July 2021) - Xu, Minhong; Pan, Guoxiang; Guo, Yuhua; Yang, Shengchen; Fang, Ze
Abstract : For improving the dispersion of iron oxide yellow pigments (FeOOH) in organic solvents, a layer of silica was coated on the surface of FeOOH, and then further modified by silane coupling agent, as a heterogeneous coating was formed on the surface of FeOOH. The modified FeOOH was characterized by TEM, XRD, IR, XPS, TG‐DTA, and zeta potential. The dispersibility of modified FeOOH under different conditions was also studied. After coating and modification, a coating layer about 5 nm was formed on the surface of FeOOH. XRD results showed that sodium silicate and KH560 modified did not change crystal structure of FeOOH, even the SiO2 coating layer existed in amorphous form. The FeOOH was bound with SiO2 and silane coupling agent by chemical bond, based on the IR and XPS analysis. The heat resistance of FeOOH was slightly improved after coating. When the amount of SiO2 modified in surface coating was 8% of the mass of FeOOH, the modification time range from 1 to 1.5 h, temperature was between 60°C and 80°C, the pH value was 7–8, and the dispersibility of FeOOH in water was significantly improved. The zeta potential test showed that the surface of FeOOH/SiO2 was negative, and its dispersibility in water was improved because the absolute value of zeta potential increased. The dispersibility of FeOOH/SiO2 was related to the structure of coupling agent. After modification with KH560, the dispersion rate increased from 14.49% to 88.0%, which improved the dispersibility in organic solvents.